2020
DOI: 10.26767/coloquio.v17i2.1679
|View full text |Cite
|
Sign up to set email alerts
|

Farming and land use changes in Cerrado biome: the case of East Maranhão – Brazil (1985/2018)

Abstract: O artigo analisou as mudanças no uso do solo na Região de Caxias, Leste do Maranhão, Nordeste do Brasil, entre os anos de 1985 e 2018. Essa delimitação encontra-se no MATOPIBA (Maranhão, Tocantins, Piauí e Bahia), parte do Cerrado. Para tanto, utilizou o mosaico de imagens do Mapbioma para detectar a localização das florestas e campos agrícolas e dos dados agropecuários fornecidos pelo IBGE. Além disso, empregou-se as informações obtidas por meio de entrevistas e questionários aplicados aos produtores de soja … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
1
5
0
2
Order By: Relevance
“…Thiago José Arruda de Oliveira, Stefan Hubertus Dorner than to soybean fields expansion (10%). These results match other studies about modern agriculture, as high-tech farmers usually expand their business based on available technology (improved seeds, machinery, and chemical inputs) and funding, instead of climate factors (OLIVEIRA et al, 2020). However, the linear regression results are statistically insignificant in the annual precipitation (mm) parameter.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Thiago José Arruda de Oliveira, Stefan Hubertus Dorner than to soybean fields expansion (10%). These results match other studies about modern agriculture, as high-tech farmers usually expand their business based on available technology (improved seeds, machinery, and chemical inputs) and funding, instead of climate factors (OLIVEIRA et al, 2020). However, the linear regression results are statistically insignificant in the annual precipitation (mm) parameter.…”
Section: Resultssupporting
confidence: 87%
“…Although, land use at Buritirana district became more intense due to soybean expansion. Even as precipitation have decreased since 2004, to monoculture farmers, at least on the short-term, such evolution seems no real obstacle for their activity, as other factors such as access to technology and funding are more decisive (OLIVEIRA et al, 2020). In contrast, small farmers of the agricultural settlements, usually cattle breeders, have been extremely dependent on stable weather conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exploratory and descriptive analysis is based on secondary data provided by relevant bodies, with the intent to ascertain farmers' responsibilities within the Campo Limpo System. Initially, it was observed that the Brazilian crop production structure is heterogeneous, even though the expansion of soybean cultivation in the last three decades brought an apparent spatial homogeneity to the Brazilian agricultural landscape (OLIVEIRA; RODRIGUES, , 2020RODRIGUES, , and 2021. To illustrate this issue, data from the 2017 Agricultural Census carried out by the Brazilian Institute of Geography and Statistics (IBGE) is used.…”
Section: Databasesmentioning
confidence: 99%
“…Although tobacco, citrus, cotton, and tomatoes are the main crops on which agrochemicals are employed (PIGNATI et al, 2017), soy has a greater share in the Campo Limpo System than other crops. That is because soy is widely diffused and it is strongly linked to large farmers, making it a key pillar of globalized agribusiness (OLIVEIRA; RODRIGUES, 2020RODRIGUES, , 2019.…”
Section: Selection Of Variables and Empirical Strategymentioning
confidence: 99%